2008
DOI: 10.1016/j.ccr.2008.09.002
|View full text |Cite
|
Sign up to set email alerts
|

A Short Nur77-Derived Peptide Converts Bcl-2 from a Protector to a Killer

Abstract: SUMMARY Bcl-2 can be converted into a pro-apoptotic molecule by nuclear receptor Nur77. However, the development of Bcl-2 converters as anti-cancer therapeutics has not been explored. Here we report the identification of a Nur77-derived Bcl-2 converting peptide with 9 amino acids (NuBCP-9) and its enantiomer, which induce apoptosis of cancer cells in vitro and in animals. The apoptotic effect of NuBCPs and their activation of Bax are not inhibited but rather potentiated by Bcl-2. NuBCP-9 enantiomers bind to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
261
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(268 citation statements)
references
References 51 publications
4
261
2
1
Order By: Relevance
“…Seminal work from the Zhang laboratory demonstrates that in cancer cells Nur77 can bind and convert Bcl-2 from a cell protector into a killer to exert its proapoptotitic function at mitochondria (7,28,49). However, our data showed that in DO11.10 T cells, Bcl-2, and Bcl-X L preserved mitochondrial membrane potential and reduced the percentage of cells undergoing apoptosis induced specifically by mitochondrialtargeted Nur77 (Fig.…”
Section: Discussioncontrasting
confidence: 54%
“…Seminal work from the Zhang laboratory demonstrates that in cancer cells Nur77 can bind and convert Bcl-2 from a cell protector into a killer to exert its proapoptotitic function at mitochondria (7,28,49). However, our data showed that in DO11.10 T cells, Bcl-2, and Bcl-X L preserved mitochondrial membrane potential and reduced the percentage of cells undergoing apoptosis induced specifically by mitochondrialtargeted Nur77 (Fig.…”
Section: Discussioncontrasting
confidence: 54%
“…A short peptide derived from the orphan nuclear receptor Nur77 was shown to bind the N-terminal regulatory region of the anti-apoptotic protein Bcl-2 and convert it into a pro-apoptotic killer protein. 58 More recently, a pro-necrotic peptide derived from Noxa, a BH3-only protein of the Bcl-2 family, was described for its capacity to induce necrosis in tumor cells in a caspase-independent manner when associated with a NRP-1-targeting peptide. 48 However, one major limitation common to both the BH3-mimetic approach and the targeting of non-BH3 sites is their strict dependency on the endogenous levels of the anti-apoptotic Bcl-2 family of proteins expressed in tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have generated overwhelming evidence that Bcl-2 is an antiapoptotic protein (1-3). However, Bcl-2 promotes apoptosis after caspase cleavage (47) or after interaction with Nur77 (28,29). Although these findings show that antiapoptotic Bcl-2 can be converted to a proapoptotic molecule, the conversion either requires caspase activation that occurs downstream of Bax-or Bak-mediated MOMP or generates a molecule whose apoptotic activity depends on Bax or Bak.…”
Section: Discussionmentioning
confidence: 53%
“…On the other hand, conversion of Bcl-2 to a proapoptotic protein has been observed in other circumstances. Upon binding to Nur77 protein or peptide, Bcl-2 undergoes conformational changes that convert it to a proapoptotic molecule with an exposed BH3 motif that neutralizes Bcl-x L and initiates apoptosis in a Bax-or Bak-dependent manner (28,29). We observed that treatment with gossypol triggered similar conformational changes in Bcl-2 that induced apoptosis in cells lacking both Bax and Bak, but the mechanism was unclear (30).…”
mentioning
confidence: 79%